Use and Misuse of Emergency Room for Children: Features of Walk-In Consultations and Parental Motivations in a Hospital in Southern Italy - Calicchio, Maria; Valitutti, Francesco; Della Vecchia, Antonio; De Anseris, Anna Giulia Elena; Nazzaro, Lucia; Bertrando, Sara; Bruzzese, Dario; Vajro, Pietro (Frontiers in Pediatrics, 2021)
Objective: Inappropriate use of emergency department (ED) represents a worldwide major issue. Herein we aimed to describe features of pediatric visits to the ED of Salerno University Hospital and to evaluate parental reasons behind the decision to walk in. Materials and Methods: We performed a retrospective observational study evaluating ED encounters for children from January 2014 to December 2019. Visits’ appropriateness was measured with a national tool assessing every ED encounter, namely “Mattoni method”, which consists in the combination of triage code assigned, diagnostic resources adopted and consultation outcomes. Moreover, 64 questionnaires were collected from a sample of parents in the waiting rooms in January 2020. Results: 42,507 visits were recorded in the study period (19,126 females; mean age ± SD: 4.3 ± 3.8 years), the majority of which were inappropriate (75.8% over the considered period; 73.6% in 2014; 74.6% in 2015; 76.3% in 2016; 76.7% in 2017; 77.9% in 2018; 75.5% in 2019). Most of the inappropriate consultations arrived at the ED by their own vehicle (94.4%), following an independent decision of the parents (97.2%), especially in at night of Saturdays/Sundays/holidays (69.7%). At multivariate analysis, younger age (O.R.: 1.11, 95% C.I. 1.06 to 1.16; p<0.0019), night visits (OR 1.39; 95% C.I.: 1.32 to 1.47; p<0.001), living in Salerno municipality (OR 1.28; 95% C.I.: 1.22 to 1.34; p<0.001), weekend day visits (OR 1.48; 95% C.I.: 1.41 to 1.56; p<0.001) and independent parental decision without previous contact with family pediatrician (OR 3.01; 95% C.I.: 2.64 to 3.44; p<0.001) were all significant independent predictors of inappropriate consultation. Hospital admission regarded 17.6% of all consultations. The questionnaire showed that most parents were aware of the non-urgency (20.3%) of the visit. The reasons for walking in were the impossibility to receive a home consultation (70%) and the difficulty in contacting their family pediatrician during weekends and holidays (54.4%), as well as the search for a quick, effective, diagnosis and therapy (48.4%). Conclusions: The study suggests a highly inappropriate use of ED for children in our region. This issue deserves considerable attention by the health care system decisors to optimally integrate hospitals and primary care.